The Goddesses and the Traveler. A reading of Parmenides’ Poem Proemium through the forms of Necessity and Legality (2006)
This text takes as its object the terms or names through which legality and necessity are presented in Parmenides’ poem proemium. An inquiry will be carried out on them, intending to restore the literary references that makes them comprehensible within th